Paradigma constitucional brasileiro da livre concorrência e da defesa do consumidor face às estruturas de poder no mercado - Peres Filho, José Augusto de Souza (2009)
The Federal Constitution of 1988, when taking care of the economical order, denotes special concern in the abuses of the economical power and the disloyal competition. The mark to mediate of all this is, in fact, the defense and the consumer's protection, once this is final addressee of whatever if it puts at the consumption market. The coming of the Law 8.078/90, Code of Protection and Defense of the Consumer, inaugurates a time of effective concern with the homogeneous individual interests originating from of the consumption relationships. In this point, the focus of main to face of the present work lives, in other words, the protection of the right to the individual property, especially manifests in the exercise of the trade freedom that keeps direct relationship with the respective social function the one that is destined. The code of the consumer's defense doesn't just take care of this, but also of the other star of the relationships of the consumption. When affirming in the interruption VI of the art. 4th that the national politics of those relationships, finds ballast in the prohibition and repression efficient of all of the abuses committed in the consumption relationships, keeping inherent relationship-causality in the economical order, sculpted for the article 170 in the Constitution of 1988. In the generic plan, the mark of the present work is to question concerning the limits of the trade freedom and previsible collisions with protection norms and the consumer's defense, as well as factual convergences of those small systems, especially in what he/she refers to the innate interests to the suppliers. In the specific plan, we aspirated to identify the protection device-commands to the actors of the trade relationship, capable to guarantee the free competition in a global economy of market, seeking especially the Well-being, for soon afterwards, in an analytical perspective, to discover the possible applications that it holds the Federal Constitution, in headquarters of economical freedoms. It was observed that the consumer today doesn't need only of laws that their needs, fruit of the vulnerability that it is him/her meditate innate. He/she lacks, yes, of effective mechanisms that prevent lesions that can be them impinged by the suppliers at the time in that you/they are useful to repair the damages when happened, punishing the author of the damage